2002
DOI: 10.3201/eid0807.010281
|View full text |Cite
|
Sign up to set email alerts
|

Bear Canyon Virus: An Arenavirus Naturally Associated with the California Mouse (Peromyscus californicus)

Abstract: Thirty-four rodents captured in southern California were studied to increase our knowledge of the arenaviruses indigenous to the western United States. An infectious arenavirus was isolated from 5 of 27 California mice but none of the 7 other rodents. Analyses of viral nucleocapsid protein gene sequence data indicated that the isolates from the California mice are strains of a novel Tacaribe serocomplex virus (proposed name “Bear Canyon”) that is phylogenetically most closely related to Whitewater Arroyo and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 22 publications
1
32
0
3
Order By: Relevance
“…To date, a total of 17 different indigenous arenaviruses have been identified in the Americas (25)(26)(27). Most of the New World arenaviruses occur in South America.…”
Section: Arenaviral Hemorrhagic Feversmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a total of 17 different indigenous arenaviruses have been identified in the Americas (25)(26)(27). Most of the New World arenaviruses occur in South America.…”
Section: Arenaviral Hemorrhagic Feversmentioning
confidence: 99%
“…Most of the New World arenaviruses occur in South America. In general, they have a rather restricted geographic distribution; and most of the viruses are associated with a single vertebrate species, usually a rodent (25)(26)(27). The natural rodent reservoirs of arenaviruses usually develop a persistent infection and continuously shed virus in their urine, feces and saliva (25,28).…”
Section: Arenaviral Hemorrhagic Feversmentioning
confidence: 99%
“…The NP and GP genes of Bear Canyon virus (BCNV), TAMV, and Whitewater Arroyo virus (WWAV) from North America have divergent phylogenetic histories. Separate analyses of full-length amino acid sequences revealed that the NPs of these three viruses are related to those of New World Group A viruses, while the GPCs are more closely related to those of New World Group B viruses [6,38,39,60]. Together, these viruses are currently regarded as a tentative Group D of New World viruses.…”
Section: Current Arenavirus Taxonomymentioning
confidence: 99%
“…1,2 Many novel arenaviruses have been reported in the literature [3][4][5][6][7] over the last decade, especially in the Americas, but the natural history and clinical importance of most of these viruses remain unclear. The family comprises 2 serocomplexes: the lymphocytic choriomeningitis-Lassa (Old World) complex and the Tacaribe (New World) complex.…”
Section: Taxonomy and Classificationmentioning
confidence: 99%